Comparative Evaluation of Transfer Function and Detailed Switching Models for a PID-Controlled Single-Phase DC–AC Conversion System - Fifin Nugroho; Hari Maghfiroh; Warindi Warindi; Fahmizal Fahmizal (Control Systems and Optimization Letters, 2026)
Transfer-function (TF) models are widely used in power electronics because of their simplicity and suitability for controller design. However, their ability to represent practical converter behavior is limited since switching actions and nonlinear effects are neglected. This paper presents a comparative evaluation of transfer-function and detailed switching models for a PID-controlled single-phase inverter system consisting of a DC–DC boost converter and a full-bridge inverter employing unipolar sinusoidal pulse width modulation (SPWM). The system is designed to convert a 46 VDC input into a regulated 220 VAC (RMS), 50 Hz output. Both models were developed in MATLAB/Simulink and evaluated under identical operating conditions. The results show that the TF model provides a computationally efficient representation suitable for preliminary controller design, while the detailed switching model captures switching-induced ripple, transient dynamics, and harmonic distortion. The detailed model achieved stable 220 VAC operation with a total harmonic distortion (THD) of 1.91%, satisfying IEEE Standard 519 requirements. The comparative analysis indicates that controller parameters obtained from the TF model can provide a useful initial tuning reference before refinement in the detailed switching model. Since the study is based exclusively on simulation, experimental validation remains necessary. The results suggest that TF models are suitable for early-stage controller development, whereas detailed switching models are required for realistic performance assessment and validation.